Anemia among Preschool-aged Children in Nepal: Variations in National Prevalence and Strength of Associated Risk Factors from 2013 to 2016. - Pasqualino, Monica. (Tufts University. Tisch Library., 2020)
This presentation describes research completed to investigate national trends in the prevalence of anemia among children 6-59 months of age and the stability of risk factors over the period 2013-2016 using data collected in the Policy and Science for Health, Agriculture and Nutrition (PoSHAN) surveys.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy